2006
DOI: 10.1016/j.virol.2006.04.044
|View full text |Cite
|
Sign up to set email alerts
|

ICP27-dependent resistance of herpes simplex virus type 1 to leptomycin B is associated with enhanced nuclear localization of ICP4 and ICP0

Abstract: It was previously shown that herpes simplex virus type 1 (HSV-1) is sensitive to leptomycin B (LMB), an inhibitor of nuclear export factor CRM1, and that a single methionine to threonine change at residue 50 (M50T) of viral immediate-early (IE) protein ICP27 can confer LMB resistance. In this work, we show that deletion of residues 21-63 from ICP27 can also confer LMB resistance. We further show that neither the M50T mutation nor the presence of LMB affects the nuclear shuttling activity of ICP27, suggesting t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 55 publications
2
30
0
Order By: Relevance
“…To investigate this possibility, Vero cells were infected with wild-type HSV-1(F), YK451 (⌬VP22), YK452 (⌬VP22-repair), YK453 (VP22LL235AA), YK454 (VP22LL235AA-repair), YK455 (VP22LL251AA), YK456 (VP22LL251AA-repair), or YK476 (⌬UL41), and the localization of ICP0 was examined at 4, 8, and 15 h postinfection, while that of ICP4, ICP8, ICP27, and VP26 was examined at 8 and 15 h postinfection. It has been shown that ICP8 localizes in the nucleus throughout HSV-1 infection, while ICP0, ICP4, ICP27, and VP26 localize predominantly in the nucleus at early times postinfection and, at later times postinfection, translocate from the nucleus to the cytoplasm and localize throughout the infected cells or predominantly in the cytoplasm (8,10,31,36,60,61). In agreement with these previous reports, ICP0 was detected mainly in the nuclei of wild-type HSV-1(F)-infected cells at 4 h postinfection.…”
Section: Characterization Of a Ul49-null Mutant Virusmentioning
confidence: 99%
“…To investigate this possibility, Vero cells were infected with wild-type HSV-1(F), YK451 (⌬VP22), YK452 (⌬VP22-repair), YK453 (VP22LL235AA), YK454 (VP22LL235AA-repair), YK455 (VP22LL251AA), YK456 (VP22LL251AA-repair), or YK476 (⌬UL41), and the localization of ICP0 was examined at 4, 8, and 15 h postinfection, while that of ICP4, ICP8, ICP27, and VP26 was examined at 8 and 15 h postinfection. It has been shown that ICP8 localizes in the nucleus throughout HSV-1 infection, while ICP0, ICP4, ICP27, and VP26 localize predominantly in the nucleus at early times postinfection and, at later times postinfection, translocate from the nucleus to the cytoplasm and localize throughout the infected cells or predominantly in the cytoplasm (8,10,31,36,60,61). In agreement with these previous reports, ICP0 was detected mainly in the nuclei of wild-type HSV-1(F)-infected cells at 4 h postinfection.…”
Section: Characterization Of a Ul49-null Mutant Virusmentioning
confidence: 99%
“…The inhibitory function was mapped to the carboxyl-terminal half of ICP27 (57,58). In more recent studies, Lengyel et al noted that leptomycin B causes massive export of ICP4 and ICP0 from the nucleus to the cytoplasm (24). They also reported that resistance to leptomycin B maps to residues 21 to 63 in the amino-terminal domain of ICP27 (24).…”
Section: Vol 82 2008mentioning
confidence: 99%
“…In more recent studies, Lengyel et al noted that leptomycin B causes massive export of ICP4 and ICP0 from the nucleus to the cytoplasm (24). They also reported that resistance to leptomycin B maps to residues 21 to 63 in the amino-terminal domain of ICP27 (24). Interestingly, the drug has no such effect in cells infected with leptomycin B-resistant mutants.…”
Section: Vol 82 2008mentioning
confidence: 99%
“…ICP27 is one of the best-characterized mRNA export factors that have been shown to favor viral RNA export and to retain cellular transcripts in the nucleus. ICP27 was shown to shuttle between the nucleus and cytoplasm through a leucine-rich nuclear export signal (16,27) via a CRM1-dependent pathway (17). Interestingly, ICP27 and UL84 share many of the same functional characteristics associated with regulatory proteins.…”
Section: Discussionmentioning
confidence: 99%